2007
DOI: 10.1093/brief-treatment/mhm028
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Mentally Abnormal Offender

Abstract: Discussions about the prediction of dangerousness, a legal or social construct, often extend beyond forensic psychiatry into the general practice of psychiatry. Dangerousness can drive the entrance to and exit from the mental health and forensic system. Better conceptualized as risk prediction, it has been seen as a core skill for forensic psychiatry and an increasing requirement for general psychiatrists. Yet, for all the expertise in and the usefulness of risk prediction, it is the daily management of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
7
0
3
Order By: Relevance
“…[13,22] However, it has been shown that a previous criminal history may increase the risk of recidivism, and thus becomes important in terms of the ongoing and future risk management of state patients. [1,23] In terms of the details of offences, it was found that the majority of offences were those committed against persons, with property offences occurring less frequently, and this is consistent with findings in the literature. [6,9] It is also an expected finding, as state patients are generally those mentally ill offenders who have committed more serious and/or violent offences.…”
Section: Articlesupporting
confidence: 85%
See 2 more Smart Citations
“…[13,22] However, it has been shown that a previous criminal history may increase the risk of recidivism, and thus becomes important in terms of the ongoing and future risk management of state patients. [1,23] In terms of the details of offences, it was found that the majority of offences were those committed against persons, with property offences occurring less frequently, and this is consistent with findings in the literature. [6,9] It is also an expected finding, as state patients are generally those mentally ill offenders who have committed more serious and/or violent offences.…”
Section: Articlesupporting
confidence: 85%
“…[6] The fact that a quarter of the state patients who were out in the community after 3 years had absconded is of concern, as they are more likely to be non-adherent to medication and to abuse substances, both factors known to increase the risk of relapse and recidivism. [18,19,23,29] Furthermore, a third of the state patients who were declared unfit to stand trial but criminally responsible for their alleged offences, were found to have absconded by the end of the 3-year study period. Although not one of the research objectives, it was considered noteworthy, as these state patients could theoretically have been referred back to the criminal justice system, after having been treated and rehabilitated, to stand trial, and then possibly prosecuted, for charges for which they were considered to be criminally responsible.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…if they pose a danger to others. 10 Chaimowitz et al 11 12 are of the opinion that medical compliance is the one most enduring factor associated with clinical stability and prevention of criminal behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Yates et al 12 are of the opinion that medical compliance is the single most enduring factor associated with clinical stability and prevention of criminal behaviour. According to Chaimowitz et al, 11 insight as well as treatment adherence are independent contributors to the risk of violence.…”
Section: Factors That May Influence Rehabilitation Management and Trmentioning
confidence: 99%